Transduction Pattern of AAVs in the Trabecular Meshwork and Anterior-Segment Structures in a Rat Model of Ocular Hypertension - Lee, Si Hyung (Mol Ther Methods Clin Dev, 2019)
Adeno-associated viruses (AAVs) are the vector of choice for gene therapy in the eye, and self-complementary AAVs (scAAVs), which do not require second-strand DNA synthesis, can be transduced into cells of the trabecular meshwork (TM). The scAAV transduction patterns in the anterior segment of normotensive eyes have been investigated previously, but those in ocular hypertensive (OHT) eyes have not. We assessed the transduction efficiencies of AAV serotypes 2, 5, and 8 in the anterior-segment structures of the eyes of Sprague-Dawley rats with OHT by circumlimbal suturing, followed 3 days later by intracameral injection of scAAV serotype 2 (scAAV2), scAAV5, or scAAV8 packaged with EGFP. The transduction of scAAV2 and scAAV5 in the TM of OHT rats was markedly enhanced after 1 month, and transduction of scAAV5 was more efficient than that of scAAV2; transduction of scAAV8 into the TM did not occur. The transduction of scAAV2, scAAV5, and scAAV8 was enhanced in the ciliary body, iris, and corneal endothelium of the OHT eyes for 3 months. The expression levels of receptors for scAAV2 and scAAV5 were significantly increased in the OHT compared with control eyes. The results demonstrated that scAAV2 and scAAV5 target the ciliary body and TM in OHT eyes, and that the OHT-related changes in anterior-segment structures enhance scAAV transduction.